The role of basic vocational education towards students employability - Ghazali @ Hassan Sulaiman; Abdul Said Ambotang (2017)
This study aims to identify the role of the curriculum of the Basic Vocational Education (BVE) to the employability of pupils in selected secondary schools in Sabah. A total of 100 respondents involved in this study with a focus on preparation for further study at the Institute of Public Skills Training (IPST) and Private Skills Training Institutes (PSTI) or preparation for entering the workforce. In addition, the objective of this study was to identify differences employability among students and identify the direction of the transformation of the relationship with the employability of vocational education and vocational skills to identify the relationship with the employability of basic education students in vocational secondary schools selected. The findings show that there are significant differences in terms of gender, nationality and course of em-ployability. While in terms of the transformation of vocational education and vocational skills showed a significant relation-ship with the employability of BVE pupils in secondary schools selected. Some proposals put forward to increase its employ-ability among students BVE at the same time ensuring appropriate courses offered by IPST and improve the level of English proficiency as well as information and communication technology literacy of students